Synthesis of Graphene Oxide Loaded Chitosan/ Hydroxypropyl Methylcellulose Bionanocomposite Films and Usage of Controlled Release of Anti-Cancer Drug 5- Fluorouracil - Akal, Mürit; Demirdere, Muhammed Emre; Ünlü, Derya (Osman SAĞDIÇ, 2021)
Controlled drug release systems have attracted a lot of attention in recent years in order to minimize the amount of drug used, to extend the period of taking drugs, and to eliminate the side effects that may occur during treatment. The main aim for using drug release is to provide a more effective treatment method. In this study, bionanocomposite films were synthesized for controlled drug release. Chitosan and hydroxypropyl methyl cellulose were used as biobased polymers. The release performances of graphene oxide loaded films were investigated by drug loading on the films. The anticancer drug 5-Fluorouracil was chosen as the model drug. Chemical bond structures of the synthesized films were determined by Fourier transform infrared (FTIR). Compatibility, miscibility and distribution of the added additives were observed by scanning electron microscopy (SEM analysis). The water swelling tests were performed because of the importanece of the degree of swelling of the films in drug release. As the amount of graphene oxide increased, the degree of swelling initially increased and then tended to decrease. While a swelling degree of 321.68% was observed in the 20% graphene oxide loaded chitosan/hydroxypropyl methylcellulose bionanocomposite film, it was 248% in the 30% graphene oxide loaded chitosan/hydroxypropyl methylcellulose bionanocomposite film. The drug encapsulation efficiency increased slightly as the amount of graphene oxide increased. The highest drug encapsulation efficiency was obtained as 69.90% in 30% graphene oxide loaded chitosan hydroxypropyl methylcellulose bionanocomposite film at the end of the 12 hours. The percentage of drug release in the same film was obtained as 9.87% at the end of 4 days. The best drug release medium was determined as pH=7.4. The results obtained showed that the synthesized films could be improved and the percentage of drug release could be increased by increasing the amount of graphene oxide.

Kontrollü ilaç salım sistemleri, kullanılan ilaç miktarını en aza indirmek, ilaç alma periyodunu uzatmak, tedavi sırasında oluşabilecek yan etkileri ortadan kaldırmak amacıyla son yıllarda oldukça ilgi görmektedir. İlaç salımının kullanılmasının temel nedeni daha etkili bir tedavi yöntemi sağlamaktır. Bu çalışmada kontrollü ilaç salımı için biyonanokompozit filmler sentezlenmiştir. Biyotemelli polimerler olarak kitosan ve hidroksipropil metil selüloz kullanılmıştır. Grafen oksit ilave edilerek katkılandırılan filmlere ilaç yüklemesi yapılarak salım performansları incelenmiştir. Model ilaç olarak antikanser ilacı 5-Fluorourasil (5-Fu) seçilmiştir. Sentezlenen filmlerin kimyasal bağ yapıları Fourier dönüşümlü kızılötesi (FTIR) ile belirlenmiştir. Polimerlerin birbiri ile uyumu, karışabilirliği, eklenen katkının dağılımı taramalı elektron mikroskobu (SEM analizi) ile görüntülenmiştir. İlaç salımında filmlerin şişme derecesi önemli olduğu için suda şişme testleri yapılmıştır. Grafen oksit miktarı arttıkça başlangıçta şişme derecesi artmış ardından düşme eğilimi göstermiştir. %20 grafen oksit katkılı kitosan/hidroksipropil metilselüloz biyonanokompozit filmde %321.68 şişme derecesi gözlenirken, %30 grafen oksit katkılı kitosan/hidroksipropil metilselüloz biyonanokompozit filmde %248.95 şişme derecesi göstermiştir. İlaç tutuklama verimi grafen oksit miktarı arttıkça çok az artış göstermiştir. En yüksek ilaç tutuklama verimi 12 saatin sonunda %30 grafen oksit katkılı kitosan/hidroksipropil metilselüloz biyonanokompozit filmde %69.90 olarak elde edilmiştir. Aynı özellikteki filmde ilaç salım yüzdesi de 4 günün sonunda %9.87 olarak elde edilmiştir. İlaç salımına ortam pH'ının etkisi incelendiğinde en iyi ilaç salım ortamının pH=7.4 olduğu görülmüştür. Elde edilen sonuçlar sentezlenen filmlerin geliştirilebilir olduğunu grafen oksit miktarının arttırılarak ilaç salım yüzdesinin arttırılabileceğini göstermiştir.
Grafen Oksit Katkılı Kitosan/Hidroksipropil Metilselüloz Biyonanokompozit Film Sentezi ve Anti-Kanser İlacı 5-Fluorourasil'in Kontrollü Salımında Kullanımı
1919B012003589
Keywords: Engineering; Mühendislik